Feasibility of Smartphone Camera Utilization and Power Point-based Video Analyzer on Kinematic Motion Experiment: An Inexpensive Method - Elisabeth Dian Atmajati; Rahmat Awaludin Salam (Universitas Sanata Dharma, 2020)
This study reports on the use of smartphone camera and power point application to analyze the kinematic motion experiment. This method is intended to make a better understanding of students concept using the tools that are commonly owned by students. The experiments performed in this study were one-dimensional (1-D) represented by falling motion and two-dimensional (2-D) using parabolic motion. In evaluating the experimental results, the obtained data were compared to the theoretical values that were calculated using analytical approach. The use of this method shows great measurement results in showing dependency of falling motion to gravitational acceleration and proofing the constant velocity at projectile motion on its horizontal plane in which it is comparable to the theoretical value. The video analyzation method also can be used as an alternative solution to the established software, even better when the higher resolution camera and frame rate was used. Noting that the tools used in the experiment were common tools around, thus, this can be used as a replacement for the advance tools.